Răspuns:
Explicație pas cu pas:
b) p(n) = 2^n -(2n+3) > 0 (1)
Pt. n=4: 16 -11 >0 se verifica
p(n+1) = 2^(n+1) - (2n +2 +3) = se verifica
2*2^n - (2n+3) -2 = 2^n - (2n+3) + 2^n -2 =
p(n) + 2^n -2 > 0 pt. ca 2^n > 2 evident
Deci p(n) ==> p(n+1), (1) e adevarata pt. orice n
c) p(n) = 3^2n + 2^(6n-5) (1)
Pt. n=1 : 9 +2 = 11 se verifica
p(n+1) = 3^(2n+2) + 2^(6n +6 -5) =
3^2*3^2n + 2^6*2^(6n-5) =
9*3^2n + 64*2^(6n-5) =
9*3^2n + 9*2^(6n-5 * 55*2^(6n-5) =
9*p(n) + 11*5*2^(6n-5) = m(11) + m(11) = m(11)
( m(11) = multiplu de 11)
Deci p(n) ==> p(n+1), (1) e adevarata pt. orice n